Interpretation of the Meaning of Hadith about the Parable of the Date-Palm Tree with A Muslims through the Tahlili Method: Interpretasi Makna Hadis Tentang Perumpamaan Pohon Kurma Dengan Seorang Muslim Melalui Metode Tahlili - Alfi Salwa (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2022)
The date palm tree is considered a tree that has great privileges because of several advantages it has. From a physical point of view, dates are able to withstand various weather conditions. Meanwhile, from a non-physical perspective, dates have many benefits, both benefits derived from their content and other benefits that arise from the parts of dates. Furthermore, this study aims to discuss the hadith about the parable of the date palm tree with the personal of the Muslims. This parable cannot be separated from the similarity of the date palm tree with the personal of the Muslims which has implications for the advantages, virtues, and benefits of the Muslims for the surrounding environment. To see the extent of these similarities, the author uses a qualitative type of research with a descriptive-analytical method. With it, the researcher will interpret the meaning of the hadith text with the help of the tahlili hadith method. The formal object of this research is the study of hadith, while the material object is the hadith about the parable of the date palm tree in the history of Bukhari no. 59. The results and discussion of this research give rise to a result related to the teaching of aqidah and moral values ​​in their relevance to faith and monotheism in Islam.